ASPEK SENTIMENTAL PADA FILM PASUKAN GARUDA I LEAVE MY HEART IN LEBANON DAN IMPLIKASINYA TERHADAP PEMBELAJARAN BAHASA DAN SASTRA INDONESIA - Endang Sulistyaniningsih; Fatimah Fatimah; As'ad As'ad (Universitas Nasional, 2021)
The Sentimental Aspects of the Garuda I Leave My Heart In Lebanon Film and Its Implications for Learning Indonesian Language and Literature. The aim of this research is to find out the Sentimental aspects of the film and its implications for Indonesian Language and Literature Learning.The method used in this study is a qualitative descriptive method with research techniques analyzing content or content analysis. Based on the results of the analysis, it can be seen from the table of findings of the sentimental aspect of the dialogue, the table of instruments for the recapitulation of the findings and the recapitulation diagram. Therefore, it can be known and concluded that the types of sentimental aspect flow in the wide screen film entitled Troops Garuda I Leave My Heart In Lebanon, the number of data findings for the type of sentimental aspect flow is 145, with the number of data from each stream, namely the active sentimental aspect flow. there are 103 findings with a total percentage of 71.03% while the number of data findings on the type of passive sentimental flow is 42 findings with a total percentage of 28.96%. The implications of the results of this research can be an inspiration, a balancer of teaching materials and as a reference source, as well as a medium for learning Indonesian language and literature for teachers/lecturers in the current digitalization era.